The Opening Up of Eastern Europe at 20-Jobs, Skills, and `Reverse Maquiladoras' in Austria and Germany - Dalia Marin (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2010)
Many people in the European Union fear that Eastern Enlargement leads to major job losses. More recently, these fears about job losses have extended to high skill labor and IT jobs. The paper examines with unique firm level data whether these fears are justified for the two neighboring countries of Eastern Enlargement Austria and Germany. We find that Eastern Enlargement leads to surprising small job losses of less than 0.5 percent of total employment in Germany and of 1.5 percent in Austria, because jobs in Eastern Europe do not compete with jobs in Austria and Germany. Low cost jobs of affiliates in Eastern Europe help Austrian and German firms to stay competitive in an increasingly competitive environment. However, we also find that multinational firms in Austria and Germany are outsourcing skill intensive activities to Eastern Europe taking advantage of cheap abundant skilled labor there. We find that the firms' outsourcing activities to Eastern Europe are a response to a human capital scarcity in Austria and Germany which has become particularly severe in the 1990s. We indeed find a reverse pattern of `Maquiladoras' emerging with Eastern Enlargement in Austria and Germany compared to what economists have found for the North American Free Trade Agreement. Skilled workers in Austria and Germany are losing from outsourcing. In both countries outsourcing contributes 35 percent and 41 percent, respectively, to changes in relative wages for skilled workers in Austria and Germany. To address the skill exodus to Eastern Europe we suggest liberalizing the movement of high skill labor.
urn:nbn:de:bvb:19-epub-11435-5
Keywords: F21; F23; J24; J31; L24; O3; P33; 330; human capital; intra-firm trade; multinationals and jobs; outsourcing to Eastern Europe; R&D policy; Auslandsverlagerung; Auslandsverlagerung; Hochqualifizierte Arbeitskräfte; Internationaler Wettbewerb; Standortwettbewerb; EU-Mitgliedschaft; Beschäftigungseffekt; Deutschland; Österreich; EU-Mitgliedschaft; Migrationspolitik; Arbeitsmigranten; EU-Staaten